From colony to nation : women activists and the gendering of politics in Belize, 1912-1982 - Macpherson, Anne S. (Engendering Latin America (Unnumbered), 2007)
The first book on women's political history in Belize, From Colony to Nation demonstrates that women were creators of and activists within the two principal political currents of twentieth-century Belize: colonial-middle class reform and popular labor-nationalism. As such, their alliances and struggles with colonial administrators, male reformers, and nationalists and with one another were central to the emergence of this improbable nation-state.